ISSUES AND CHALLENGES OF FINANCIAL MANAGEMENT PRACTICES IN ISLAMIC FINANCIAL INSTITUTIONS: EMPIRICAL EVIDENCE FROM BANGLADESH - Islam, Serajul; Mamun, Abdullahil; Islam, K. M. Anwarul; Uddin, Mohammad Rahim; Sultana, Tania (Indian Journal of Finance and Banking, 2021)
Studies suggest several issues and challenges of financial management practices in Islamic banks and insurance companies and Islamic non-bank financial institutions (INBFIs) in Bangladesh. The purpose of the research is to examine the issues and challenges of Islamic Financial Management (IFM) from an empirical perspective. The study relies on a structured questionnaire survey in prominent Islamic financial institutions (IFIs) of Bangladesh for achieving its objective. After confirming data reliability based on Cronbach's alpha, the study proceeds to analyse by applying descriptive statistics and principal component factor analysis using correlation, Kaiser-Meyer-Olkin (KMO) and Bartlett's Test and VARIMAX Rotation. The study finds that there is no separate regulatory framework to supervise and monitor IFIs in Bangladesh rather the central bank regulates the Islamic financial system based on the existing laws and regulations of the conventional financial system. The findings of this study suggest that the government should establish a separate regulatory body for monitoring the IFI’s functions so that they can perform their activities smoothly in the congenial environment in Bangladesh.JEL Classification Codes: G10, G21, G23.